A titanium redox-switch enables reversible C-C bond forming and splitting reactions - G. Jafari, Mehrafshan; Fehn, Dominik; Sandoval-Pauker, Christian; Gau, Michael R.; Meyer, Karsten; Pinter, Balazs; Mindiola, Daniel J.; Reinholdt, Anders (Chemical Science, 2025)
Using an Earth-abundant transition metal to mediate formation and splitting of C-C σ-bonds, in response to electrical stimuli, constitutes a promising strategy to construct complex organic skeletons. Here, we showcase how [nBu4N][N3] reacts with an isocyanide adduct of a tetrahedral and high-spin TiII complex, [(TptBu,Me)TiCl] (1), to enact N-atom transfer, C-N bond formation, and C-C coupling, to form a dinuclear complex, [(TptBu,Me)Ti{AdN(N)C-C(N)NAd}Ti(TptBu,Me)] (3), with two TiIII ions bridged by a disubstituted oxalimidamide ligand (nBu = n-butyl, TptBu,Me = hydrotris(3-tert-butyl-5-methylpyrazol-1-yl)borate, Ad = 1-adamantyl). Magnetic and computational studies reveal two magnetically isolated d1 TiIII ions, and electrochemical studies unravel a reversible two-electron oxidation at −0.87 V vs. [FeCp2]0/+. Despite these observations, chemical oxidation of 3, ultimately, leads to rupture of the oxalimidamide moiety with C-C bond splitting to form [(TptBu,Me)Ti{1,3-μ2-AdNCN}2Ti(TptBu,Me)][B(C6F5)4]2 (4), which displays an antiferromagnetically coupled Ti2III,III configuration, mediated by superexchange through its bridging carbodiimide ligands. A comparative reactivity study of isocyanide toward a transient vanadium nitride [(TptBu,Me)V 00000000000000000 00000000000000000 00000000000000000 01111111111111110 00000000000000000 01111111111111110 00000000000000000 01111111111111110 00000000000000000 00000000000000000 00000000000000000 N(THF)] (5) gives further insight into the structure of putative intermediates involved in the coupling sequence.